Baduy Rituals: Jampe and Mantra Exploring the Traditional Life Practices of the Sundanese Wiwitan Religion - Al Ayubi, Sholahuddin; Hudaeri, Mohamad (Aqlania, 2023)
This study examines the traditional rituals of the Baduy community related to the use of jampe and mantra as an integral part of Sundanese Wiwitan religious life. Sunda Wiwitan, as a local belief of the Baduy people, contains spiritual values, local wisdom, and traditions that have been passed down from generation to generation. Jampe rituals and mantras have an important role in various aspects of life, from traditional ceremonies to traditional medicine to the practice of self-protection. This study uses a qualitative approach with ethnographic methods to explore the symbolic meaning, social function, and relevance of jampe and mantras in maintaining harmony between humans, nature, and Sang Hyang (God Almighty). The findings of the study show that these rituals not only reflect the cultural identity of the Baduy people but also become a medium to preserve spiritual ties with ancestors and maintain the sustainability of natural ecosystems. This research contributes to the understanding of the importance of preserving local traditions as part of Indonesia's cultural heritage and the relevance of these rituals in the context of modern life.